A Study To Analyze The Adoption Of Augmented Reality & Virtual Reality And Impact Of Artificial Intelligence On Real Estate Sector In India - Venkata Satya Kiran, Patchala Lakshmi (Digital Repository of Theses, 2025)
Digital technologies are developing very fast, thereby revolutionizing various sectors in the world, and the real estate industry in India is not an exception. As the sophisticated tools like Augmented Reality (AR), Virtual Reality (VR), Artificial Intelligence (AI) are being implemented, a major shift in the manner properties is being marketed, sold off and managed has been witnessed. Such technologies guarantee interaction and immersion, which makes it possible to see the features of properties in remote locations and maximise the performance of developers and realtors and their contact with customers. The aim of existing study is “to identify and analyse key factors influencing the adoption and application of AR, VR and AI technologies in the real estate sector; to investigate opportunities and challenges using AI and VR & AR in the real estate sector in India; to examine the role of augmented reality, virtual reality, and artificial intelligence in improving marketing and sales strategies in the Indian real estate sector and to evaluate the potential implications of adopting artificial intelligence and augmented & virtual reality technologies in real estate in India.” The respondents for this research are the buyers from cities (Bangalore, Hyderabad, and Chennai) in India. So, Bangalore, Hyderabad, and Chennai are universe for this study. The study pattern will be of randomly selected sample using purposive sampling technique within the population selected. The explored target is to 600 samples tentatively from area of the population in the present study. Overall, the results that all the tables give indicate that there is a high appreciation of the potential role of AR, VR, and AI as strategic tools of enhancing marketing and sales in real estate sector in India. The technologies provide unrivalled ways to improve customer interaction, brand awareness, organizational decision-making, and openness. Nevertheless, the industry will face the problem of infrastructure preparedness, training, affordability, and safety to make integration successful. The solutions to these barriers should be targeted towards cost optimization, user trainings, and the creation of industry-wide standards, which should be pursued in the future. When deployed responsibly AR, VR, and AI not only revolutionise the marketing and selling strategies but also have the potential to revolutionise the customer experiences as well, setting the stage of a more digital, transparent and customer centric recently in India. Keywords: artificial intelligence (AI), augmented reality (AR), digital technologies, real estate, virtual reality (VR)